Bacillary angiomatosis and Kaposi's sarcoma in skin lesion of HIV positive patient (Actualizaciones en Sida e Infectología, 2023)
Bacillary angiomatosis (BA) is a rare infectious disease, caused by bacteria of the genus Bartonella spp, transmitted by vectors such as fleas, lice and mosquitoes. It causes different clinical syndromes in humans. In patients with human immunodeficiency virus (HIV) infection with an LT CD4 +